AB0663 Neurological involvement in primary sjÖgren syndrome. (23rd January 2014) - Teixeira, F.; Moreira, I.; Silva, A.M.; Vasconcelos, C.; Farinha, F.; Santos, E.
Abstract : Background: Primary Sjögren Syndrome (pSS) is an autoimmune disorder characterized by a chronic lymphocytic and plasmacellular infiltration of exocrine glands and extraglandular features including both peripheral nervous system and central nervous system involvement. However, the diagnosis of pSS with neurologic involvement is sometimes difficult and specially central nervous system manifestations have been rarely described. Objectives: To perform an observational retrospective cross-sectional case–control study to evaluate prevalence, clinical patterns and outcomes of neurological involvement in a cohort of pSS patients followed up in a single centre. Methods: A total of 91 pSS patients (88 females, 3 male) with a mean age 47, 6 years, diagnosed according to the 2002 criteria proposed by the American–European Consensus Group, were evaluated for neurological involvement after exclusion of secondary causes. Demographic, clinical, immunological data were compared between patients with and without neurological involvement. Neuroimaging data and peripheral nerve conduction study with quantitative sensory testing were also analysed. Results: Neurological involvement was detected in 24 (26, 4%) patients (all females). The mean age at disease onset and neurological onset were 41, 8 and 47, 9 years, respectively. Neurologic involvement frequently preceded the diagnosis of pSS in 10 (42%) patients. Fifty (n=12) patients had peripheral system involvement (PNS), 46% (n=11) patients had CNS disorders and 4% (n=1) patients had both PNS and CNS involvement. In patients with PNS involvement, pure sensory neuropathy (small fiber neuropathy confirmed by quantitative sensory testing and sural neuropathy) occurred most frequently (n=5), followed by cranial nerve involvement affecting trigeminal, facial, or trochlear nerves (n=4). Multiple mononeuropathy (n=1), sensorimotor polyneuropathy (n=1), autonomic neuropathy (n=1) and myasthenia gravis (n=1), were also observed. In patients with CNS disorders, headache with MRI abnormalities compatible with inflammatory disease (n=3) occurred most frequently. Spinal cord involvement (n=2), seizures (n=2), motor and sensory deficit (n=2), movement disorders (n=2), aseptic meningitis (n=1) were the other manifestations observed. Cognitive dysfunction was observed in 3 of these patients. Headache was reported in nine patients other than the three mentioned above. The Raynaud's phenomenon was more common in these patients (p=0, 04).The frequency of constitutional symptoms (such as fever and fatigue) and lung involvement was significantly higher (p<0, 05) in pSS with neurological involvement than in pSS without neurological involvement and the articular symptoms were significantly less frequent (p<0, 05) in pSS with neurological involvement. There was no statisticalsignificance in other factors parameters between the two groups. The neurologic outcome was good in 58% (n=14) patients. Conclusions: Our results showed that neurological complications were present in 26, 4% of all patients with pSS. In other series, it was reported a lower prevalence of neurological complications. Maybe it was due to missed diagnosis or differente methodologies. In our cohort, the CNS involvement had similar frequency to PNS involvement. This result is quite different from that of previous studies where PNS involvement was mainly described. Disclosure of Interest: None Declared